The impact of globalization on the conflict of laws approach (Journal of Imam Al-Kadhim College, 2024)
Private International Law (PIL) rules have played a crucial and significant role in regulating private international legal relationships in the face of globalization. Since their adoption, they have consistently provided legal solutions to address this phenomenon. However, in today's world, which can be described as an era of hyper-globalization, the emergence of modern communication technologies and artificial intelligence has led to the widespread use of cross-border contracts.